Aescin – a natural soap for the formation of lipid nanodiscs with tunable size. Issue 7 (7th January 2021) - Geisler, Ramsia; Pedersen, Martin Cramer; Preisig, Natalie; Hannappel, Yvonne; Prévost, Sylvain; Dattani, Rajeev; Arleth, Lise; Hellweg, Thomas
Abstract : The article discusses the temperature-dependent reorganization of beta-aescin stabilized lipid nanodiscs from smaller, to larger discs, ribbons and finally to stacks of sheets. Abstract : The saponin β-aescin from the seed extract of the horse chestnut tree Aesculus hippocastanum has demonstrated a beneficial role in clinical therapy which is in part related to its strong interaction with biological membranes. In this context the present work investigates the self-assembly of nm-sized discoidal lipid nanoparticles composed of β-aescin and the phospholipid 1, 2-dimyristoyl- sn-glycero -3-phosphocholine (DMPC). The discoidal lipid nanoparticles reassemble from small discs into larger discs, ribbons and finally stacks of sheets upon heating from gel-phase to fluid phase DMPC. The morphological transition of the lipid nano-particles is mainly triggered by the phospholipid phase state change. The final morphology depends on the phospholipid-to-saponin ratio and the actual temperature. The study is conducted by small-angle X-ray scattering (SAXS) and transmission (TEM) and freeze fracture electron microscopy (FFEM) are used to cover larger length scales. Two different models, representing a disc and ribbon-like shape are applied to the SAXS data, evaluating possible geometries and molecular mixing of the nano-particles. The stacked sheets are analysed by the Caillé theory.